(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Relevance. The problem of autism spectrum disorders is one of the most urgent in modern psychiatry, which is due to the steady increase in the number of children suffering from early childhood autism. Recently, the number of patients diagnosed with autism has increased, partly due to changing approaches to diagnosis. One of the main priorities of the national policy in the field of mental health of children and adolescents is to work to reduce disability due to mental illnesses by preventing the development of mental disorders and developmental disorders in children [2,3]. Materials and methods of research. The following methods were used in the work: clinical-dynamic, clinical-psychopathological, catamnestic tracking, psychological testing. The first group includes children who attend kindergartens and schools with a special approach. Было включено 45 childrenей with a diagnosis of RDA were included. Who are diagnosed with forms of early childhood autism with a continuously sluggish and paroxysmal course (procedural autism - 11, Kanner syndrome - 12, Asperger’s syndrome-8, schizoid disorder -5). Results and discussions. According to L. Wing (1981) and M. Rutter (1983), specific pathological features of cognitive processes occupy a central place in the structure of autism syndrome. All other abnormal manifestations are associated with the primary pathology of cognitive activity.